Perceived relative income and preferences for public good provision - Anca Balietti; Angelika J. Budjan; Tillmann Eymess (University of Heidelberg, Department of Economics, 2023)
Guided by a theoretical framework, we study how perceived relative income affects preferences for public goods. In a randomized survey experiment, we inform respondents from India of their official income rank and elicit preferences for air quality, including actual contributions to environmental initiatives. Right-wing supporters withdraw contributions when perceived relative income increases. The effect coincides with diminished health concerns and lower intentions to utilize private protection measures against air pollution. In contrast, center-left supporters do not reduce contributions. A second survey experiment demonstrates the causality of the relationship using a novel treatment that exogenously shifts relative income perceptions.
urn:nbn:de:bsz:16-heidok-334239
Keywords: C83; D31; H41; I14; O15; Q53; 330; perceived relative income; public goods; voluntary contributions; airpollution